The Green Knowledge and Green Awareness Influences Analysis on Green Behavior and Its Impact on Green Lifestyle of Instant Noodles Consumer - Hadriana, Hadriana; Hudrasyah, Herry (The Indonesian Journal of Business Administration, 2013)
Changing in the consumer' behavior because of the growing of the people nowadaysin era modernization makes the consumers become more time conscious and want everything to be practical. That is why food such as instant noodles is become more and more popular these days because of its practical. Unfortunately, this instant noodles made by packaging product's plastic material which have many negative impact to the environment. The purpose of this research is to improve the quality of human and environmental value by proposing green strategy for instant noodles companies in Indonesia. The research in this thesis was made to get to know if the knowledge and awareness of instant noodles' consumer about global warming will have impact to their behavior which will lead to a green lifestyle. The finding of this research then can be use to plan the instant noodles company to apllying green business strategy on their company.Keywords: Green, Knowledge, Awareness, Behavior, Lifestyle.